SISTEM PENGOLAHAN DATA JAMAAH UMROH BERBASIS WEB MENGGUNAKAN METODE INTERPOLATION SEACRH PADA PT.KAISA ROSSIE SEMARANG - Eko Siswanto; Arif Iskandar; Syamsul Ma’arif (Universitas Islam Nahdlatul Ulama Jepara, 2019)
The use of software as a supporting tool to input data in a company is needed. The software that is used of course must also be able to work effectively and efficiently so that it can support the performance of administrative staff. Every company, private institution or government has certainly done a filing process to store files or data that are considered important. Archiving data on pilgrims performed at this company is still centralized in several Microsoft Excel files for all staff staff. Search is needed to find specific information from a table when the exact location of that information was previously unknown.When the array data is ordered with key values,searching data can be useful using method interpolation search for efficient to find a key value from data array. The system development method used in this system is the Research And Development (R & D) method. This study purpose is intended to be able to assist the task of the cashier in inputting data and admin in making reports given to the leadership, and information appropriate to the position of the employee.